Two new species of the genus Proboscidopirates (Hemiptera: Heteroptera: Enicocephalidae) from Madagascar with a list of the species - Baňař, Petr; Štys, Pavel; Rahanitriniaina, Sahondra Lalao; Rabotoson, Marie Estherine (Zootaxa, 2014)
Two new species Proboscidopirates ericguilberti sp. nov. Baňař & Štys and Proboscidopirates rugulosus sp. nov. Baňař & Štys are described from central-east Madagascar. A list of Proboscidopirates species is given. Potential thelytoky of this endemic Madagascan genus, some of its generic and species-specific dignostic characters and its distribution relative to that of Oncylocotis Stål species are discussed.